The revolt of the masses - Gasset, Jose Ortega Y (The new American Library, 1952)
Social upheaval in early 20th-century Europe is the historical setting for this seminal study by the Spanish philosopher, Jose Ortega y Gasset. Continuously in print since 1932, Ortega's vision of Western culture as sinking to its lowest common denominator and drifting toward chaos brought its author international fame and has remained one of the influential books of the 20th century.